The Influence of the Temperature on Effectiveness of Selected Disinfectants Against African Swine Fever Virus (ASFV) - Małgorzata Juszkiewicz; Marek Walczak; Grzegorz Woźniakowski; Zygmunt Pejsak; Katarzyna Podgórska (Viruses)
African swine fever (ASF) is one of the most economically significant diseases of pigs caused by African swine fever virus (ASFV). Due to the lack of effective and safe vaccines, one of the crucial measures to protect farms from the introduction of the ASFV is to apply a strict regime of biosecurity and disinfection. However, in field conditions, the activity of disinfectants may be influenced by temperature, resulting in reduced activity or biodegradation (i.e., freezing or evaporating). The aim of this study was to evaluate the effect of a wide range of temperatures on the virucidal activity of selected active substances commonly used against ASFV. Eight active substances were tested, namely: sodium hypochlorite (1.0%), glutaraldehyde (0.1%), potassium peroxysulfate (0.5%), caustic soda (1.0%), phenol (1.0%), acetic acid (3.0%), benzalkonium chloride (1.0%), and formaldehyde (0.4%). The virucidal activity of each compound was tested at different temperatures (21, −10, and −20 °C for 30 min) and compared to the initial virus titer under the same temperature conditions. Exposure to a range of temperatures did not significantly affect the virucidal efficacy of tested active substances against ASFV. Most of the evaluated substances had reduced virus titers ≥ 4 log10, regardless of the temperature. However, two of them (benzalkonium chloride and acetic acid) were sensitive to sub-zero temperatures, showing a lack of the required 4 log10 virus titer reduction. The conducted study showed that temperature could hamper the virucidal effect of selected substances (i.e., benzalkonium chloride and acetic acid), showing their moderate efficacy against ASFV −10 °C and −20 °C. The results suggest that extreme caution should be taken while applying these substances at sub-zero temperatures. The other substances had no significant sensitivity to the temperature range. Nevertheless, in the case of freezing the agent, insufficient penetration of the disinfected surface may occur, which may result in an ineffective disinfection process.